The impact of monetary systems on income inequity and wealth distribution: A case study of cryptocurrencies, fiat money and gold standard - Othman, Anwar Hasan Abdullah; Syed Jaafar Alhabshi, Syed Musa; Kassim, Salina; Abdullah, Adam; Haron, Razali (Emerald, 2020)
Purpose – This study uses the autoregressive distributed lag model (ARDL) econometric approach to investigate empirically the effects of cryptocurrencies, the gold standard and traditional fiat money on global income inequality measured based on the Gini coefficient, and various ratios of income inequality distribution such as top 1 per cent, top 10 per cent, top 40 per cent and top 50 per cent. Design/methodology/approach – The study uses the ARDL econometric approach. Findings – The findings indicated that cryptocurrency and gold standard monetary systems contributed significantly to reducing global inequality of income and wealth distribution. Conversely, the traditional fiat money system contributes positively to global income and wealth inequality while also contributing significantly to their fluctuation. Practical implications–Thissuggeststhatthefiatmonetarysystemresultsinthecoerciveredistributionof income and wealth if governments pursue a social welfare policy. They must resolve this conflict between the current fiat monetary system and social policy by opting for an alternative monetary system such as cryptocurrency or gold standard. These alternative monetary systems offer the promise of resolving the incomeandwealthinequalityassociatedwiththetraditionalmonetarysystemwhichareaccompaniedwiththe channels of inflation, lack of financial inclusion and debt creation, and to offer a more sustainable financial system. Originality/value – The study recommends that monetary policy must be revisited to account for its direct effect on income and wealth redistribution to achieve social welfare goals.